2003
DOI: 10.1017/s0140525x03000025
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of biological and psychological perspectives on cognitive coordination in schizophrenia

Abstract: Cognitive neuroscience provides a new conceptual framework for psychiatry by showing how psychological processes arise from neuronal activity (Kandel 1998). Conversely, it is possible that psychiatry will influence the future development of cognitive neuroscience by encouraging a better balance between localist and holistic conceptions of brain function. An apparent conflict between these conceptions has been central to the development of neuroscience, with the emphasis upon locally specialized functions emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
314
1
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 378 publications
(349 citation statements)
references
References 533 publications
16
314
1
15
Order By: Relevance
“…We will therefore re-assess the hypothesis that impairment of contextual modulation is such a pathophysiology. For an introduction to and commentary on an earlier version of that hypothesis see Phillips and Silverstein (2003).…”
Section: Introductionmentioning
confidence: 99%
“…We will therefore re-assess the hypothesis that impairment of contextual modulation is such a pathophysiology. For an introduction to and commentary on an earlier version of that hypothesis see Phillips and Silverstein (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Communication and coordination failures between different brain regions may account for a wide range of problems in schizophrenia, from psychosis to cognitive dysfunction (Phillips and Silverstein, 2003). The phenomenology of schizophrenia suggests a disturbance in integration of brain activity through loss of "inner unity" (Kraepelin, 1919) or "cognitive coordination" (Phillips and Silverstein, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenology of schizophrenia suggests a disturbance in integration of brain activity through loss of "inner unity" (Kraepelin, 1919) or "cognitive coordination" (Phillips and Silverstein, 2003). It has been hypothesized that many of the deficits in schizophrenia can be attributed to core abnormalities in the timing, synchronization, and efficiency of neural processes that bind and integrate information from different brain regions, as measured by EEG (Green and Nuechterlein 1999;Spencer et al 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they provide evidence that there are variations in those rhythms and mechanisms across cortical regions, so we now need to discover the computational, cognitive, and psychopathological consequences of such variations. Finally, it was agreed that the theories of Friston (1999) and of Phillips and Silverstein (2003) have much in common. Friston suggested that the "disconnection" theory of schizophrenia could be referred to as the "dysconnection" theory.…”
Section: Dynamic Coordination In Cognition and Behaviormentioning
confidence: 93%
“…Prima facie, NMDA receptors (NMDARs) seem to function as highly selective gain controllers, and thus could help mediate coordination within the cognitive system (Phillips and Singer, 1997). This hypothesis is supported by evidence that NMDAR malfunction or dysregulation is a crucial part of the pathophysiology of cognitive disorganisation in psychosis (Phillips and Silverstein 2003).…”
Section: Dynamic Coordination In Local Cortical Microcircuitsmentioning
confidence: 99%